Peran Sulawesi Selatan dalam Strategi Lumbung Pangan BIMP-EAGA (BIMP-EAGA Food Basket Strategy) - Zulkhair Burhan (WANUA : Jurnal Hubungan Internasional, 2015)
AbstractAs a province member in sub-regional BIMP-EAGA cooperation that also become as a centre of agriculture production in East Indonesia, South Sulawesi is trying to make serious efforts to contribute in ASEAN Food Basket Program. In this research explained that South Sulawesi government implementing a program called Program Lumbung Pangan Masyarakat (people food basket program) as response to Food Basket Strategy that agreed in frame of BIMP-EAGA cooperation. This also indicate that sub-national actor, in this case is province, has important contribution to build cooperation in regional scheme of cooperation.